To what extent english reading background during the college level affects students´ academic writing skill?”. / presentado por Yenis Rosibel Acosta Casco, Roberto Carlos Arévalo, Cruz María Gámez Gámez ; docente director Lic. Manuel Alexander Landaverde Castillo. - Acosta Casco, Yenis Rosibel; Arévalo, Roberto Carlos; Gámez Gámez, Cruz María; Landaverde Castillo, Manuel Alexander; Ayala Edgar Nicolas (San Salvador, El Salvador : Universidad de El Salvador, 2014)
Reading to write is a task that not all people practice even the students at the university are not considering that reading can help them to write better. Of course it cannot be generalized since there are many students in our country and schools that read for pleasure to increasing their knowledge something that is applied and reflected in written documents. Many of the students at the University of El Salvador have some troubles to write an acceptable composition due to the lack of bases to follow because students have not read any kind of material before writing. In other words, the population of the FLD has no the habit of reading. They are not conscious about the benefits that reading has. For that reason, students face many problems such as word order, organization, spelling and so on when taking the English Composition Courses. Reading is an important skill in order to improve many other skills such as writing since they cannot occur separately.
Bibliografia 70 - 75
Keywords: Inglés -- Enseñanza